The Response of Globe Artichoke Plants to Potassium Fertilization Combined with the Foliar Spraying of Seaweed Extract - Spyridon A. Petropoulos; Rokayya Sami; Nada Benajiba; Reda M. Y. Zewail; Mustafa H. M. Mohamed (Agronomy, 2022)
This work investigated the effects of potassium mineral fertilizers, combined with biofertilizers (T1–T4 treatments) and the foliar spraying of seaweed extract (at 1 g/L, 2 g/L, and 3 g/L) on the vegetative growth characters, chemical constituents of foliage, and the yield and quality parameters of globe artichoke. The maximum height, and the fresh and dry weight of the leaves, was recorded in plants that received only soil with added potassium (T1 treatment) and sprayed with seaweed extract at 3 g/L. Furthermore, the highest number of offshoots per plant was registered in the T2 treatment combined with seaweed extract (3 g/L). T1 and T2 treatments resulted in the highest values of leaf N, P, K, and total carbohydrate content when combined with seaweed extract (3 g/L). The highest numbers of early, late, and total heads per plant were obtained for the T1 treatment and seaweed extract (3 g/L). Similarly, most of the head quality parameters were beneficially affected by the T2 treatment and seaweed extract (3 g/L). In conclusion, it is suggested that soil application of mineral potassium fertilizer (75% of RD) combined with biofertilizer (25% of RD) and the foliar spraying of seaweed extracts at 3 g/L, was most beneficial for the yield and quality parameters of globe artichoke plants.